2023
DOI: 10.3390/ijerph20065004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of a Garden Plant Smellscape from the Perspective of Perceptual Interaction

Abstract: The purpose of this study was to investigate the physiological recovery effects of olfactory, visual and olfactory–visual stimuli associated with garden plants. In a randomized controlled study design, ninety-five Chinese university students were randomly selected to be exposed to stimulus materials, namely the odor of Osmanthus fragrans and a corresponding panoramic image of a landscape featuring the plant. Physiological indexes were measured by the VISHEEW multiparameter biofeedback instrument and a NeuroSky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that the α-band increased due to aromatherapy [19], positive sound stimulation [20], listening to Mozart music [21], and audio-visual relaxation [22]. Another report indicated that olfactory-visual stimuli increased α-band and β-band [23]. Furthermore, it was reported that α power was correlated with resilience [24], and a correlation was observed between α peak frequency and calm score [25].…”
Section: Effects On Imagery and Somatosensory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that the α-band increased due to aromatherapy [19], positive sound stimulation [20], listening to Mozart music [21], and audio-visual relaxation [22]. Another report indicated that olfactory-visual stimuli increased α-band and β-band [23]. Furthermore, it was reported that α power was correlated with resilience [24], and a correlation was observed between α peak frequency and calm score [25].…”
Section: Effects On Imagery and Somatosensory Activitymentioning
confidence: 99%
“…α is a frequency component of 8-13 Hz, which often appears mainly in the back of the head when the person is at rest with eyes closed and in a relaxed state. β is a frequency component of [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz and a brain wave that often appears during an awake state. δ (delta) waves (0.5-< 4 Hz) and θ (theta) waves (4-< 8 Hz) have lower frequencies than alpha waves; therefore, they are considered slow waves and are noted during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of aromatic compounds on the brain in multi-sensory environmental interventions are thought to be directly mediated. Thus, smellscape is considered an important healing element in horticultural therapy, applied to comprehensive health outcomes including mental health, physical health, reduced agitation behavior, improved cognitive function, and improved well-being [30,31].…”
Section: Introductionmentioning
confidence: 99%